Biophysical Constraints to Robusta Coffee Productivity in Low, Moderate, and High Rainfall Areas - Winfred Nabiteeko Nakyagaba; Herbert Talwana; Samuel Kyamanywa; Godfrey H. Kagezi; Yazid Bamutaze; David Mfitumukiza; Revocatus Twinomuhangi; Hannington Bukomeko; David Mukasa; Bernard Fungo; van Asten Piet; Laurence Jassogne (International Journal of Agronomy)
Globally, coffee (Coffea spp.) is a major commodity in terms of production and trade. Although Uganda is seventh among the major producing countries, yields remain low at 500 kg/ha. Understanding the biophysical constraining factors is vital to inform efforts toward closing the yield gap. A diagnostic study was conducted in 150 coffee fields to determine the most yield-limiting factors under varying rainfall thresholds, categorized as low ≤ 1100 mm/year, moderate ≥ 1100 to 1200 mm/year, and high ≥ 1200 mm/year. Robusta yield, soil parameters, pest and disease proportions, and tree and banana intercrop densities were measured under the thresholds. Parametric methods and the boundary line approach were used to analyze limiting factors and yield gaps. The results indicated that yields were significantly (p<0.001) higher in moderate (960 ± 234 kg ha−1) than low (803 ± 188 kg ha−1) and high (713 ± 193 kg ha−1) rainfall thresholds. The proportion of pests and diseases doubled in high than low rainfall thresholds. Soil parameters and tree or banana intercrop were the main yield-limiting factors. Magnesium limited yield in 47%, 26%, and 14% of coffee fields, causing 23%, 20%, and 21% yield gaps in high, moderate, and low thresholds, respectively. The maximum yield was 1492 kg ha−1; the explainable yield gap was 32%. A larger yield gap of 42%, 36%, and 32% was observed in high, moderate, and low rainfall thresholds. Therefore, long-term integrated soil fertility and tree or banana intercrop management are suggested for high thresholds, focusing on pests and diseases in moderate and low rainfall thresholds. Additionally, frequent field monitoring is needed to determine the prevalence of pests and diseases at different times of the year and season. Hence, matching thresholds of rainfall variability to the Robusta coffee yield is critical for closing the yield gap and achieving Uganda’s anticipated 20 million 60-kg bags year−1.